Impact of ACE Units and Geriatrics Consults on Adherence to the 4Ms and Patient Outcomes - Sandra Zeng; Julia Adler‐Milstein; Robert Thombley; James D. Harrison; Melody Luo; W. John Boscardin; Sarah Ngo; Stephanie Rogers (Journal of the American Geriatrics Society, 2026)
ABSTRACT Background The Age‐Friendly Health Systems (AFHS) movement, guided by the 4Ms framework has been widely adopted to improve care for older adults. While specialized inpatient models such as Acute Care for Elders (ACE) units and Geriatrics Consults aim to improve outcomes, gaps remain in understanding how these models align with 4Ms adherence and their relationship to patient outcomes. Methods We conducted a retrospective observational study of 28,833 hospital encounters for patients aged ≥ 65 at an academic health system. Encounters were categorized into four groups: Usual Care, Geriatrics Consult, ACE Unit, and ACE Unit and Consult. Adherence to each M and a composite 4Ms score was derived from 16 process measures. Outcomes included falls, length of stay, discharge to a facility, and 30‐day readmissions. Multivariable regression was completed to assess the relationship between 4Ms adherence and health outcomes. Results Patients receiving any Geriatrics clinical model had higher overall 4Ms adherence than usual care. High 4Ms adherence was associated with lower readmissions in the Consult Only group but higher readmissions in the ACE + Consult group. Facility discharge rates increased with high adherence in Consult and ACE + Consult groups. No group differences were observed in falls. ACE Unit patients with high adherence showed shorter lengths of stay, whereas Consult groups had longer stays. Conclusion Inpatient Geriatrics models improve adherence to Age‐Friendly care practices, but their effects on outcomes are mixed.